2020
DOI: 10.3389/fpsyt.2020.563287
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Paternal and Maternal Depression During the Perinatal Period: A Systematic Review and Meta-Analysis

Abstract: Background: Meta-analyses suggest an increased prevalence of paternal depression during the perinatal period of around 10%. The relationship between paternal and maternal symptoms, however, has received little attention.Objective: To determine pooled estimates pertaining to the relationship between paternal and maternal depression during the perinatal period according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement.Data sources: Studies reporting on the relationship between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
1
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 73 publications
4
36
1
4
Order By: Relevance
“…There is also evidence for higher rates of anxiety disorders during pregnancy in both mothers and fathers (27). Further, maternal and paternal anxiety and depressive disorders appear to be correlated, and may even accumulate in couples (15,28,29). Some studies have also found support for paternalspecific course patterns.…”
Section: Introductionmentioning
confidence: 99%
“…There is also evidence for higher rates of anxiety disorders during pregnancy in both mothers and fathers (27). Further, maternal and paternal anxiety and depressive disorders appear to be correlated, and may even accumulate in couples (15,28,29). Some studies have also found support for paternalspecific course patterns.…”
Section: Introductionmentioning
confidence: 99%
“…There may also be benefits for the mental health of mothers enrolled in HV if their partner receives FAB. Paternal depression has been consistently associated with elevated maternal depression (Paulson and Bazemore, 2010;Thiel et al, 2020), and persistence of maternal postpartum depression has been shown to be directly influenced by the presence of depression in their partners (Vismara et al, 2016). Thus, implementation of FAB in conjunction with MB may allow HV programs to more effectively address maternal depression than through their usual services, or their usual services enhanced only with mental health interventions that are maternal-focused.…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence rates estimate that 5-13% of fathers will experience depression during their partner's pregnancy and the first year postpartum (Paulson and Bazemore, 2010;Cameron et al, 2016;Pace et al, 2016), with a recent meta-analysis indicating that prior mental illness and paternal unemployment were the strongest predictors of paternal depression, with financial instability, limited social support, and low level of paternal education also associated (Ansari et al, 2021). Two meta-analyses have also highlighted positive, moderate correlations between paternal depression and maternal depression (Paulson and Bazemore, 2010;Thiel et al, 2020). The transition into fatherhood itself has been associated with an increase in depressive symptoms of as much as 68% in the first 5 years after the birth of the child (Garfield et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Befunde verweisen bspw. auf ein erhöhtes Risiko, an depressiven Symptomen zu leiden, wenn dies im Peripartalzeitraum bereits beim Partner nachgewiesen ist [47]. Im schlimmsten Fall entsteht bei Paaren so eine besonders hohe Belastung, die sich nachteilig auf die Beziehungsqualität und das Verhältnis zum Kind auswirken kann [48][49][50].…”
Section: Diskussionunclassified